2015
DOI: 10.1371/journal.pone.0134802
|View full text |Cite|
|
Sign up to set email alerts
|

Methods for Improving Human Gut Microbiome Data by Reducing Variability through Sample Processing and Storage of Stool

Abstract: Gut microbiome community analysis is used to understand many diseases like inflammatory bowel disease, obesity, and diabetes. Sampling methods are an important consideration for human microbiome research, yet are not emphasized in many studies. In this study, we demonstrate that the preparation, handling, and storage of human faeces are critical processes that alter the outcomes of downstream DNA-based bacterial community analyses via qPCR. We found that stool subsampling resulted in large variability of gut m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
241
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 35 publications
9
241
3
1
Order By: Relevance
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 90%
“…The impact of the type of fecal sample collection method on microbial data has been considered in a number of previous studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, the majority of these studies were conducted in North American or European populations near academic or clinical laboratories and typically included only a small number of methods.…”
mentioning
confidence: 99%
“…Investigators in a number of previous studies have assessed different collection methods for fecal samples and the impact of leaving a sample at room temperature on the fecal microbiome (10,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The FOBT card, or a similar Whatman FTA card (GE Healthcare Life Sciences, Pittsburgh, Pennsylvania), has been tested in a few studies (10,21,26,32).…”
Section: Discussionmentioning
confidence: 99%
“…RNAlater has also been tested in a number of studies (10, 20-24, 26, 30, 32), but the results varied. The majority of studies concluded that RNAlater was an acceptable preservative for microbial analyses of fecal samples (10,22,23,26,30), although in some studies, researchers detected decreased alpha diversity (20,21,30), decreased DNA purity or yields (21,24), or lower stability at room temperature for longer periods (33) compared with immediately frozen fecal samples. Storage of fecal samples in 70% ethanol does not appear to be suitable for microbiome analyses (10), but 95% ethanol has been previously observed to adequately preserve fecal samples (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies, such as the study conducted by Zhu et al (15), used patients with no history of antibiotics, probiotics, proton pump inhibitors, and histamine receptor antagonists within 3 mo before examining the fecal microbiota; however, others did not consider all of these precautions. In addition, the collection and processing of fecal samples have been shown to produce large variances and inaccuracies in the interpretation of the taxa present in the microbiota (48), which may be a contributing factor to the conflicting data found in NAFLD microbiome studies. Even so, all of these studies have evaluated the association, and well-designed studies are needed to unravel any causal relation between the gut microbes and NAFLD.…”
Section: Introductionmentioning
confidence: 99%